Happiness and Wellness - Biopsychosocial and Anthropological Perspectives 2023
DOI: 10.5772/intechopen.106297
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and Happiness: The Causes and Consequences of Gratitude

Abstract: In this chapter, we review recent research on the relationship between gratitude and happiness. First, we show how gratitude is a critical component of the good life. Because gratitude is vital to wellbeing, it is important to establish the causes of state and trait gratitude. We explain an appraisal approach to grateful emotion and show how certain benefit interpretations are critical to the experience of gratitude. In this context, we describe an encouraging new paradigm that has been applied to the study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In accordance with the SDHS statistical bipolar property, this also suggests that these people will have lesser levels of depression. This result is consistent with theory and the majority of previous research demonstrating that individuals with greater gratitude are happier 32 and have lower levels of depression. 28 , 29 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the SDHS statistical bipolar property, this also suggests that these people will have lesser levels of depression. This result is consistent with theory and the majority of previous research demonstrating that individuals with greater gratitude are happier 32 and have lower levels of depression. 28 , 29 …”
Section: Discussionsupporting
confidence: 92%
“…Watkins et al 32 have put forth the amplification theory of gratitude, positing that the act of psychologically magnifying the positive aspects of one’s life can lead to an augmentation of happiness. In addition, individuals with a heightened disposition towards gratitude tend to engage in a favorable reinterpretation of negative experiences, thereby eliciting feelings of gratitude.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study verified a structural equation model that revealed the relationship between gratitude disposition and life satisfaction, which is a factor in subjective well-being [ 11 ]. Watkins et al explored the cause and effect relationship between gratitude and happiness based on various studies and theories and suggested that gratitude can improve happiness [ 12 ]. Therefore, in the field of positive psychology, attempts have been made to use gratitude as a clinical intervention to promote individuals’ well-being and happiness [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, happiness can be both a cause and consequence of gratitude [ 12 ]; there are many positive things that can make people feel happy, which makes them feel grateful. Therefore, in this study, it was assumed that if grateful disposition is high, there is more social support, which results in people feeling happy.…”
Section: Introductionmentioning
confidence: 99%